Modifikasi dan Inovasi Ikan Bandeng Menjadi Produk Olahan Basreng - La Ode Muhammad Zainul; Andri Satria Wijaya (Abdimas Universal, 2024)
Community service in the form of making processed basreng products from milkfish was carried out by the RT 01 women's group and the cadre women's group in Gersik Village, Penajam District, North Penajam Paser Regency, East Kalimantan Province. In this activity, the producer's aim is to provide new business ideas for MSMEs or some communities by utilizing the results of local milkfish cultivation into a processed product in the form of basreng, which is a new innovation for local business actors and can become a new business idea. The making of processed basreng was carried out in PAUD which is not used in RT 01. This activity was carried out for 1 day on Monday, 19 February 2024. In this activity, the service team explained how to make this basreng product using milkfish as ingredients and also shared together. with mothers about this product. This is done so that the product created can become a new business innovation that does not yet exist in the Gersik sub-district area. The result of making this product is to provide a new idea and be able to taste the basreng product itself so that it can be resold and can advance the economy of the surrounding environment.